Synthesis and characterization of ZnO and ZnO : Ga films and their application in dye-sensitized solar cells - Goncalves, Agnaldo de Souza [UNESP]; Davolos, Marian Rosaly [UNESP]; Masaki, Naruhiko; Yanagida, Shozo; Morandeira, Ana; Durrant, James R.; Freitas, Jilian Nei; Nogueira, Ana Flavia (Royal Soc Chemistry, 2008)
Highly crystalline ZnO and Ga-modified zinc oxide (ZnO:Ga) nanoparticles containing 1, 3 and 5 atom% of Ga3+ were prepared by precipitation method at low temperature. The films were characterized by XRD, BET, XPS and SEM. No evidence of zinc gallate formation (ZnGa2O4), even in the samples containing 5 atom% of gallium, was detected by XRD. XPS data revealed that Ga is present into the ZnO matrix as Ga3+, according to the characteristic binding energies. The particle size decreased as the gallium level was increased as observed by SEM, which might be related to a faster hydrolysis reaction rate. The smaller particle size provided films with higher porosity and surface area, enabling a higher dye loading. When these films were applied to dye-sensitized solar cells (DSSCs) as photoelectrodes, the device based on ZnO: Ga 5 atom% presented an overall conversion efficiency of 6% (at 10 mW cm(-2)), a three-fold increase compared to the ZnO-based DSSCs under the same conditions. To our knowledge, this is one of the highest efficiencies reported so far for ZnO-based DSSCs. Transient absorption (TAS) study of the photoinduced dynamics of dye-sensitized ZnO:Ga films showed that the higher the gallium content, the higher the amount of dye cation formed, while no significant change on the recombination dynamics was observed. The study indicates that Ga-modification of nanocrystalline ZnO leads to an improvement of photocurrent and overall efficiency in the corresponding device.